2022
DOI: 10.17582/journal.pjz/20201104131155
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Anti-Diabetic Effect of Gamma-Irradiated Pumpkin Seeds

Abstract: Authors' Contribution All authors contributed to the study design. YZ, SR and MX collected samples and analyzed the data. YZ prepared the first draft of the manuscript. YZ, NLand XZ performed the experiments. CH and XN revised the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Due to the presence of these bioactive nutrients, it is assumed to be used as a remedy for lowering blood cholesterol or depression [ 13 , 14 ]. Besides that, anti-diabetic, antiulcer, wound healing, antioxidant, and hepatoprotective properties of the seed of pumpkin have also been investigated [ [15] , [16] , [17] ]. The fresh leaves and flowers also harbor important bioactive compounds with pharmacological activities such as antimicrobial, antifungal, anti-mutagenic, antioxidant, hepato-protection, anti-hyperglycemic, antidepressant, and anti-inflammation [ 9 , [18] , [19] , [20] ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the presence of these bioactive nutrients, it is assumed to be used as a remedy for lowering blood cholesterol or depression [ 13 , 14 ]. Besides that, anti-diabetic, antiulcer, wound healing, antioxidant, and hepatoprotective properties of the seed of pumpkin have also been investigated [ [15] , [16] , [17] ]. The fresh leaves and flowers also harbor important bioactive compounds with pharmacological activities such as antimicrobial, antifungal, anti-mutagenic, antioxidant, hepato-protection, anti-hyperglycemic, antidepressant, and anti-inflammation [ 9 , [18] , [19] , [20] ].…”
Section: Introductionmentioning
confidence: 99%
“…It is proved that natural antioxidants are more effective as well as possess no harmful effect on human health in comparison with synthetic ones [ 16 ]. Natural antioxidant compounds including carotenoids, tocopherols, flavonoids, phenolic acids, vitamin C, and some minerals are mostly found in vegetables and fruits [ 6 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal thyroid hormone levels have also been reported in diabetic patients by Gursoy and Tuncel (1999). Abdul Azeem et al (2021) have similarly reported decreases in thyroid hormone levels in alloxan induced diabetic male Wistar rats which were restored to normal upon stabilization of the blood glucose with γ-irradiated pumpkin seeds dried powder administration. The lowered T4 level observed in both reversed diabetic and diabetic animals' groups may reflect the selective effect of diabetes on thyroid hormone that may not be dependent on glucose gradation.…”
Section: -Discussionmentioning
confidence: 93%
“…The irradiation does not have a substantial impact on the irradiated fungal mycelium (Duan et al, 2010). This increase can be associated with the radiation dose, as it was found that high doses of radiation led to an expansion in TPC and TF in pumpkin (Abdul Azeem et al, 2022).…”
Section: Phenols Flavonoids Total Soluble Sugars and Reducing Sugarsmentioning
confidence: 99%